2021
DOI: 10.3390/vaccines9121475
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SARS-CoV-2-Specific Antibodies in Human Milk after mRNA-Based COVID-19 Vaccination and Infection

Abstract: SARS-CoV-2-specific antibodies are secreted into human milk of infected or vaccinated lactating women and might provide protection to the breastfed infant against COVID-19. Differences in antibody response after these types of exposure are unknown. In this longitudinal cohort study, we compared the antibody response in human milk following SARS-CoV-2 vaccination or infection. We analyzed 448 human milk samples of 28 lactating women vaccinated with the SARS-CoV-2 vaccine BNT162b2 as well as 82 human milk sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Women who recovered from SARS-CoV-2 infection in pregnancy and were subsequently vaccinated during the lactation period had the highest antibody levels in breast milk compared to those only infected or vaccinated. This is consistent with previous studies in human milk ( Juncker et al, 2021 ) as well as in serum ( Gils et al, 2021 , Manisty et al, 2021 ) where just one dose of the BNT162b2 vaccine elicited significantly higher antibody levels in previously infected participants. We showed a positive correlation between SARS-CoV-2 antibody levels in serum and in human milk, in line with previous studies ( Demers-Mathieu et al, 2021 , Gonçalves et al, 2021 , Whited and Cervantes, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…Women who recovered from SARS-CoV-2 infection in pregnancy and were subsequently vaccinated during the lactation period had the highest antibody levels in breast milk compared to those only infected or vaccinated. This is consistent with previous studies in human milk ( Juncker et al, 2021 ) as well as in serum ( Gils et al, 2021 , Manisty et al, 2021 ) where just one dose of the BNT162b2 vaccine elicited significantly higher antibody levels in previously infected participants. We showed a positive correlation between SARS-CoV-2 antibody levels in serum and in human milk, in line with previous studies ( Demers-Mathieu et al, 2021 , Gonçalves et al, 2021 , Whited and Cervantes, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…In a fifth study (40) (n = 26) one or more side effects were reported by 57% of the participants after the first dose. After the second dose, one or more side effects were reported by 81% of the participants.…”
Section: Side-effects In the Mother After Covid-19 Vaccination During...mentioning
confidence: 97%
“…Of the 30 included references, 1 study reports on the excretion of COVID-19 components in breast milk (17), 20 studies report on the excretion of antibodies in breast milk (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), 1 study report on the excretion of other immunological factors (37) and 1 study reports on the impact of vaccination on breast milk production (38). Two studies report on both side effects and the excretion of COVID-19 antibodies (39,40), 1 study reports on the excretion of COVID-19 antibodies and the excretion of vaccine components (41), 3 studies report on side effects and the impact of vaccination on breast milk production (42)(43)(44)) and 1 study reports on side effects, the impact of vaccination on breast milk production and on breast milk production (45).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Human milk antibodies are suggested to play an important role in the protection against respiratory infections (2)(3)(4)(5). Antibodies against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been found in human milk after maternal infection and vaccination (6)(7)(8)(9)(10)(11)(12). It is very likely that these antibodies play a critical role in protecting the infant against COVID-19.…”
Section: Introductionmentioning
confidence: 99%